2020
DOI: 10.1002/adom.201901548
|View full text |Cite
|
Sign up to set email alerts
|

A Tunable Metasurface with Switchable Functionalities: From Perfect Transparency to Perfect Absorption

Abstract: A thin screen exhibiting dynamically switchable transmission/absorption functionalities is highly desired in practice. However, a trilayer transmissive metasurface with active elements controlled in a uniform manner cannot exhibit independently controlled transmission and absorption properties due to intriguing interplays between the scattering and absorbing properties in systems exhibiting inversion symmetries. This motivates to employ the coupled‐mode theory to establish a generic phase diagram for such tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(95 citation statements)
references
References 39 publications
0
90
0
Order By: Relevance
“…Control over these complex coefficients, locally or globally, can give rise to a multitude of tunable functionalities and respective applications, for example, absorber, polarizer, anomalous reflector, etc. Fundamental physical properties of the resonant unit cells underlie the operation regimes, that is, when a reflective metasurface can operate as a tunable absorber/ reflector [10,11] or when a transmissive metasurface is transparent/absorptive, [12] as well as the transitions between them, [13] as can be shown with, for example, coupled mode theory.…”
Section: Introductionmentioning
confidence: 99%
“…Control over these complex coefficients, locally or globally, can give rise to a multitude of tunable functionalities and respective applications, for example, absorber, polarizer, anomalous reflector, etc. Fundamental physical properties of the resonant unit cells underlie the operation regimes, that is, when a reflective metasurface can operate as a tunable absorber/ reflector [10,11] or when a transmissive metasurface is transparent/absorptive, [12] as well as the transitions between them, [13] as can be shown with, for example, coupled mode theory.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, multilayer meta-atoms were widely used to build transmissive metasurfaces. In [42][43][44], multilayer meta-atoms are explained by the coupled-mode theory, which reveals the inherent physics governing the transmission properties in multilayer meta-atoms of distinct types. It is found that meta-atoms with a particular type can provide transmission phases covering only a particular range.…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, the geometric-phase metasurfaces are intrinsically multifunctional, since they may merge deflection and polarization manipulation in one step, e.g., see [48,55,56]. The tunable and reconfigurable metasurfaces may enable even more diversity in terms of functionality [57][58][59][60]. Nevertheless, the capability of the structures which do not comprise tunable components in multifunctional operation is also very high.…”
Section: Introductionmentioning
confidence: 99%